"How can I gain skills if I don't practice?" The dynamics of prohibitive silence against pre-marital pregnancy and sex in Zimbabwe. - Jeremiah Chikovore; Lennarth Nystrom; Gunilla Lindmark; Beth Maina Ahlberg (PLoS ONE)
Young people face sexual and reproductive health (SRH) problems including Human immunodeficiency virus (HIV) and Acquired immunodeficiency syndrome (AIDS). It is critical to continue documenting their situation including the contexts they live in. As part of a larger study that explored perspectives of men to SRH and more specifically abortion and contraceptive use, 546 pupils (51% female; age range 9-25 years) from a rural area in Zimbabwe were invited to write anonymously questions about growing up or other questions they could not ask adults for fear or shame. The pupils were included following descriptions by adults of the violence that is unleashed on unmarried young people who engaged in sex, used contraceptives, or simply suggested doing so. The questions by the young people pointed to living in a context of prohibitive silence; their sexuality was silenced and denied. As a consequence they had poor knowledge and their fears and internal conflicts around sexuality and pregnancy were not addressed. Current action suggests concerted effort at the policy level to deal with young people's SRH in Zimbabwe. It nevertheless remains necessary, as a way to provide support to these efforts, to continue examining what lessons can be drawn from the past, and how the past continues to reflect in and shape present dynamics and relations. There is also need to look more critically at life skill education, which has previously been described as having failed to address adequately the practical needs of young people. Life skill education in Zimbabwe has rarely been systematically evaluated. A fuller understanding is also needed of the different factors co-existing in contemporary African societies and how they have been and continue to be constituted within history, and the implications to the promotion of adolescent SRH.